Comparison of high gain power conditioners for photovoltaic applications with suitable maximum power point tracking - M, Rekha.; M, Kowsalya. (International Journal of Engineering and Technology, 2018)
In this paper, a comparative study of high gain step-up converters of different topologies is taken place. Due to the increase in pollution, a shift towards a green energy is opted. The Photo Voltaic (PV) system is chosen as a source for the converters. To harvest maximum power from the PV, a suitable Maximum Power Point Tracking (MPPT) technique is adapted. The different converters taken into considerations are Conventional Boost converter, Full Bridge Converter, Dual Active Bridge Converter and Single- Ended-primary-Inductor Converter SEPIC. The major goal of this paper is to extract high gain from the converter with minimum PV output. The complexity among the converters is analyzed and this comparison reveals the best converter for the PV system. The converters are simulated using MATLAB/Simulink.Â Â